The Beatings Will Continue Until Morale Improves. (August 2017) - Herrmann, Andrew F.
Abstract: Political decisions about higher education and organizational decision-making within higher educational institutions reflect the acceptance of academic capitalist discourse, placing financial burdens on students, stress upon faculty, and the obliteration of trust between faculty and administration. In this critical layered narrative account, a tenure-track faculty member examines the impacts and influences of academic capitalism, including how this neoliberal discourse disregards the idea of higher education as a public good, creates an atmosphere of fear among faculty, and affects faculty-student relationships. This account illustrates how academic capitalism, with its emphasis on money and power, influenced decisions regarding a partnership with a software company, and of course, a rebooted football program.